The new normal? Cluster farming and smallholder commercialization in Ethiopia - Dureti, Guyo Godana; Tabe-Ojong, Martin Paul Jr.; Owusu-Sekyere, Enoch (Wiley, 2023)
Cluster farming is increasingly recognized as a viable means of improving smallholder economic integration and commercialization in many developing countries. However, little is known about its impact on smallholder welfare and livelihoods. We examine the relationship between cluster farming and smallholder commercialization using a large-scale survey of 3969 farm households in Ethiopia cultivating high-acreage crops such as teff, wheat, maize, barley, and sesame. Using switching regressions and instrumental variable estimators, we show that cluster farming is associated with commercialization measured as commercialization index, market surplus value, and market price. To further deal with endogeneity concerns, we also employ some pseudo-panel models where we observe similar insights. Beyond this, we account for heterogeneities by disaggregating households based on farm scales and crops cultivated. Our findings show that cluster farming is positively associated with commercialization for all farms and crop types despite this disaggregation. However, the related gains are higher among medium and large farms and vary per crop type. These findings imply that cluster farming is crucial in improving smallholder commercialization and may be a critical entry and leveraging point for policy. We thus lend support to initiatives and plans that seek to upscale cluster farming as they can potentially improve smallholder commercialization with ensuing impacts on rural livelihoods and welfare.